1998
DOI: 10.1007/bf02919391
|View full text |Cite
|
Sign up to set email alerts
|

Observation of geometric structure of collagen molecules by atomic force microscopy

Abstract: Atomic force microscopy was used to study the geometric structure of collagen fibrils and molecules of rat calcanean tendon tissues. The authors found that the diameter of the fibrils ranged from 124 to 170 nm, and their geometric form suggested a helical winding with spectral period from 59.4 to 61.7 nm, close to the band dimensions reported by electron microscopy. At high magnification, the surface of these bands revealed images that probably correspond to the almost crystalline array of collagen molecules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
3
18
0
2
Order By: Relevance
“…Therefore, we have imaged type lll collagen in fluid using tapping mode atomic force microscopy. Our results are similar to previous atomic force microscopic investigations of type l collagen (Arango et al, 1995;Baranauskas et al, 1998;Baselt et al, 1993;Chernoff and Chernoff, 1992;Gale et al, 1995;Revenko et al, 1994). The assembly of type I collagen fibrils as visualized by atomic force microscopy was previously reported by Gale and co-workers (1995).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, we have imaged type lll collagen in fluid using tapping mode atomic force microscopy. Our results are similar to previous atomic force microscopic investigations of type l collagen (Arango et al, 1995;Baranauskas et al, 1998;Baselt et al, 1993;Chernoff and Chernoff, 1992;Gale et al, 1995;Revenko et al, 1994). The assembly of type I collagen fibrils as visualized by atomic force microscopy was previously reported by Gale and co-workers (1995).…”
Section: Resultssupporting
confidence: 93%
“…Previous atomic force microscopic investigations have described the structure (Aragno et al, 1995;Baranauskas et al, 1998;Baselt et al, 1993;Bigi et al, 1997;Chernoff and Chernoff, 1992;Fujita et al, 1997;Gathercole et al, 1993;Meller et al, 1997;Raspanti et al, 1997;Revenko et al, 1994;Shattuck et al, 1994;Yamamoto et al, 1997) and assembly of type l collagen (Gale et al, 1995) in vitro, as well as its in vivo appearance in cornea and sclera (Fullwood et al, 1995) and humeral head articular surface (Jurvelin et al, 1996). The ultrastructural appearance of fibrous long spacing collagen has also been elucidated by atomic force microscopy (Paige et al, 1998).…”
Section: Resultsmentioning
confidence: 93%
“…Since AFM scans only the sample surface, our method did not reveal the inner 'lacework' observed in [11,33]. Generally, we observed clustered fibrils as also seen in [9,15,22]. Thus, we took an approach similar to that of Garcia et al [30], in which several particles were imaged in a single scan for data analysis; we did not attempt to image single fibrils as in [10,23,24,34].…”
Section: Atomic Force Microscopy: Artifacts and Modelsmentioning
confidence: 74%
“…Clinical studies quantifying structural differences in fibrillar collagens between control (Table 1) and diabetic (Table 2) humans and rats [9][10][11][12][13][14][15][16] have employed scanning and transmission electron microscopy (SEM and TEM) and atomic force or scanning probe microscopy (AFM or SPM, referred to hereafter as AFM). The first evidence of the presence of larger collagen fibril diameters in diabetic sciatic nerve was presented by Muona et al [16] who measured endoneurial collagen fibrils in spontaneously diabetic BioBreeding (BB) rats using TEM.…”
Section: Collagens In Diabetic Neuropathymentioning
confidence: 99%
“…Flint et al (1984) studied the diameter of collagen fibrils from various parts of the skin of various species, and suggested a correlation between the distribution of the fibrils, biochemical conditions and the functional load acting on the tissue. Thereafter variable diameter of collagen fibrils has been reported in various tissues including cartilage (Howlett, 1979 ;Kostovic Knezevic et al 1981 ;Wright & Youson, 1983 ;Mizuno et al 1990 ;Kuc & Scott, 1994), subepithelial connective tissue (Hino et al 1982 ;Ottani et al 1998 ;Sato, 1998), eye (Waring & Rodrigues, 1980 ;Pac et al 1989 ;Yamabayashi et al 1991 ;Shauly et al 1992 ;Meek & Leonard, 1993 ;Meller et al 1997), peripheral nerve (Muona et al 1989 ;Baerwald et al 1991 ;Abe et al 1995), skeletal muscle (Gabella, 1991 ;Yoshihara et al 1993 ;Nishimura et al 1994) and tendon (Gotoh & Sugi, 1985 ;Neurath & Stofft, 1992 ;Baranauskas et al 1998 ;Kobayashi et al 1999), as shown in the Table. These data show that collagen fibrils generally have a large diameter in tendons and sclera where they are obviously exposed to strong mechanical stress.…”
Section: Variations In the Diameter Of Collagen Fibrilsmentioning
confidence: 99%